Ethical leadership in project-based organizations of Pakistan: the role of psychological empowerment and Islamic work ethics. Issue 3 (9th August 2021) - Mubarak, Namra; Khan, Jabran; Safdar, Samyia; Muhammad, Shah; Riaz, Asim
Abstract : Purpose: This study aims to examine the relationship between ethical leadership and project success directly and indirectly through psychological empowerment along with the moderating role of Islamic work ethic. Design/methodology/approach: Using a time-lagged design, data were gathered from 202 employees working in project-based organizations of Pakistan. Confirmatory factor analysis confirmed the distinctiveness of variables used in the study. Findings: Consistent with the cognitive evaluation theory, the findings supported the hypotheses other than the moderating role of Islamic work ethics between psychological empowerment and project success. The results confirmed that ethical leadership promotes project success directly and indirectly via psychological empowerment. Furthermore, theoretical and practical implications are also discussed highlighting the importance of ethical leadership for researchers and practitioners. Originality/value: Literature is insufficient on the topic of ethical leadership in the project management domain with the effect of Islamic work ethics and psychological empowerment. Therefore, the current study explored unanswered research questions in the project management domain.